EXTRAPOLATING THE ROLE OF TRANSFORMATIVE CONSTITUTIONALISM IN THE DECOLONISATION AND AFRICANISATION OF LEGAL EDUCATION IN SOUTH AFRICA (The Pretoria Student Law Review, 2021)
This article extrapolates the role of transformative constitutionalism in the decolonisation and African of legal education in South Africa. In a constitutionally mandated transformative context, the systematic approach to the decolonisation and Africanisation of legal education advanced in this article emanates from the four drivers of curriculum transformation set out in the 2017 document entitled ‘Reimagining curricula for a just university in a vibrant democracy — Work stream on curriculum transformation at the University of Pretoria’. These four drivers are: responsiveness to social context; epistemological diversity; renewal of pedagogy and classroom practices; and an institutional culture of openness and critical reflection. Presently, South African universities do not have an existing national framework for a decolonised and Africanised legal education. The article therefore argues that the UP Document contains valuable guidelines on curriculum transformation of legal education as it resonates well with the objectives of both the National LLB Standard and transformative constitutionalism itself. As result, the universities which offer legal education in conjunction with key stakeholders and role-players in the legal fraternity can incorporate its valuable guidelines in National Review of the LLB programme through a proper design of constitutionally transformed framework for a decolonised and Africanised legal education.
Keywords: Africanisation; curriculum transformation; decolonisation; legal education; South Africa; transformative constitutionalism